The wooden sea - Carroll, Jonathan 1949- (New York, NY Tom Doherty Associates, LLC, 2001)
In the small town of Crane's View, New York, "a three-legged dog limps into the comfortable life of Police Chief Frannie McCabe and drops dead at his feet," and then "a mysterious, multicolored feather ... keeps insinuating itself into his past, present, and future."--Jacket.
"A Tom Doherty Associates book."